Free-flap Treatment of Congenital Pressure Necrosis of the Forearm in the Neonate - Son, Ji; Medalie, Daniel A. (Journal of Reconstructive Microsurgery Open, 2016)
Background Microvascular surgery is not commonly performed in pediatric or neonatal populations, and when it is performed, it is done with some trepidation due to small size of the vessels, prolonged anesthesia, vasospasm, and difficult postoperative care. We describe microsurgical reconstruction of full-thickness loss of the forearm tissue in a 2-week-old due to congenital necrosis.Methods A male infant was born with blistering of the ulnar aspect of the forearm. Removal of necrotic tissue resulted in a defect of 60% of his forearm skin and musculature with exposed ulna, ulnar nerve, and artery. Soft tissue defect was reconstructed using rectus free flap and split-thickness skin graft from the buttock.Results The flap and graft survived without complication and the patient demonstrated a completely healed wound.Conclusion With advances in operative microscopes, instruments, surgical techniques, and anesthetic techniques, free tissue transfer in the neonate is feasible despite small vascular caliber. An experienced surgical team remains one of the most important factors to obtain a good outcome.
Keywords: microsurgery; neonatal microvascular reconstruction; congenital pressure necrosis